The Influence of Limestone And Calcium Hydroxide Addition in Asphalt Concrete Mixture - Danny, Gunaran; Y., Nasus K.; Napitupulu, Josep P. F; Makmur, Amelia (ComTech: Computer, Mathematics and Engineering Applications, 2016)
As time passes, flood often occurs in the area of Gunung Sahari, Jakarta Utara. The flood damages concrete asphalt mixture and it needs particular improvement. Therefore, the purpose of this research is to know the effects of the added combination of limestone and calcium hydroxide on concrete asphalt mixture as a filler resistant to flood. Concrete asphalt mixture that filled with the combination of limestone and calcium hydroxide is a mixture that is made with non-uniform aggregat gradations, filler and liquid asphalt mixed and solidified in a heat state. Limestone and calcium hydroxide mixture is used because both materials included in the most numerous sedimentary rock. Concrete asphalt mixture with the filler combination of limestone and calciumhydroxide is made with optimum asphalt 5.4%, one variation level of limestone (15%), and calcium hydroxide (15%), and three variation levels of fillers (5%, 7.5%, and 15%) to get optimum asphalt levels and filler levels that are compatible with flood condition. Based on optimum asphalt 5.4% towards aggregate total weight and combined level of limestone and calcium hydroxide suitable for the conditions, 8.75 % towards fine aggregate weight. The characteristic value of limestone and calcium hydroxide mixture in maximum condition is VIM 4.55%, VMA 18.83%, stability 1031.26 kg and flow 4.93 mm, where the characteristic value meets the established specifications standard by Pekerjaan Umum Bina Marga. From the result, it is showed that the use of the mixture can decrease the value of stability and increase the value of flow, compared with asphalt and filler with normal levels.